Management and Psychological Aspect: Teenagers' Awareness of Privacy in Social Media - Eni Maryani; Detta Rahmawan; Irma Garnesia; Reksa Anggia Ratmita (Ikatan Sarjana Komunikasi Indonesia, 2020)
Rising concern about the impact of internet usage among teenagers needs to be continuously addressed. Teenagers’ awareness of online privacy was the focus of this study on account of frequent sharing of private information in social media. This study is an exploratory research which tries to map and understand the psychological and cultural aspects of vulnerable online privacy practice by teenagers. The data were collected through a survey and interviews with high school students in Bandung, Indonesia. This study found that teenagers’ knowledge, awareness, and management of online privacy was relatively low. Psychologically, teenagers often need others to talk to. To maintain relationship, some cultural aspects, such as togetherness, friendliness, and openness to strangers were perceived as important. However, those aspects were the causes of poor online privacy practices. A call for increased media literacy and the development of cyber law that can anticipate internet-based crime especially against teenagers, were discussed.